2013
DOI: 10.1083/jcb.201301115
|View full text |Cite
|
Sign up to set email alerts
|

Rap1 potentiates endothelial cell junctions by spatially controlling myosin II activity and actin organization

Abstract: Rap1 potentiates endothelial cell junctions by spatially controlling non-muscle myosin II activity through activation of the Cdc42–MRCK pathway and suppression of the Rho–ROCK pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
158
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(173 citation statements)
references
References 59 publications
(108 reference statements)
8
158
1
Order By: Relevance
“…In endothelial cells, MRCK is activated upon induction of cell-cell contacts and controls how compact and aligned circumferential bundles are towards junctions [86]. However, in this model, Tuba is not involved, but a different GEF (FGD5) is recruited to activate Cdc42 and MRCK, thereby promoting linear endothelial junctions [86].…”
Section: Different Hues Of the Same Colourmentioning
confidence: 99%
See 1 more Smart Citation
“…In endothelial cells, MRCK is activated upon induction of cell-cell contacts and controls how compact and aligned circumferential bundles are towards junctions [86]. However, in this model, Tuba is not involved, but a different GEF (FGD5) is recruited to activate Cdc42 and MRCK, thereby promoting linear endothelial junctions [86].…”
Section: Different Hues Of the Same Colourmentioning
confidence: 99%
“…A likely candidate is MRCK, a kinase effector of Cdc42, that associates with acto-myosin filaments and, similar to ROCKI/II, phosphorylates myosin regulatory chain [85]. In endothelial cells, MRCK is activated upon induction of cell-cell contacts and controls how compact and aligned circumferential bundles are towards junctions [86]. However, in this model, Tuba is not involved, but a different GEF (FGD5) is recruited to activate Cdc42 and MRCK, thereby promoting linear endothelial junctions [86].…”
Section: Different Hues Of the Same Colourmentioning
confidence: 99%
“…VE-cadherin promotes Rho-kinase activity, MLC phosphorylation and actomyosin contractility, which, in turn, enhances VE-cadherin accumulation at cell junctions and thereby vessel stability 33,34 . The small GTPase Rap1, another important regulator of endothelial junction formation 35 , has been recently shown to promote VE-cadherin-dependent cell-cell adhesion through Cdc42, the kinase MRCK, MLC phosphorylation and actin reorganization 36 .…”
Section: Inducible Inactivation Of Itgb1 In the Postnatal Endotheliummentioning
confidence: 99%
“…As a follow up, the same group showed that Rap1 activates Cdc42 through the Rho-GEF FGD5. 81 This includes the local phosphorylation of myosin light chain (MLC) by the myotonic dystrophy-kinase related Cdc42-binding kinase (MRCK). Interestingly, a study by the Bos lab showed that Rap1 activation results in inhibition of RhoA activity, releasing tension from the junction region and thereby promoting stabilization of endothelial cell-cell junctions.…”
Section: Endothelial Adherens Junction Control By Rho Gtpasesmentioning
confidence: 99%